HBR guide to delivering effective feedback. (Harvard Business Review Press, 2016)
HBR Guide to Delivering Effective Feedback provides you with practical advice and tips to transform any performance discussion―from weekly check-ins to annual reviews―into an opportunity for growth and development. You’ll learn to: Establish trust with your direct reports Assess their performance fairly;Emphasize improvement, even in criticism;React calmly to a defensive feedback recipient;Recognize and motivate star performers;Create individualized development plans.